Reduced white matter integrity and disrupted brain network in children with type 2 and 3 spinal muscular atrophy - Huirong Nie; Shasha Lan; Huan Wang; Pei Xiang; Mengzhen Yan; Yang Fan; Wanqing Shen; Yijuan Li; Wen Tang; Zhiyun Yang; Yujian Liang; Yingqian Chen (Journal of Neurodevelopmental Disorders)
Abstract Background Spinal muscular atrophy (SMA) is caused by reduced expression of survival motor neuron (SMN) protein. Previous studies indicated SMA causes not only lower motor neuron degeneration but also extensive brain involvement. This study aimed to investigate the changes of brain white matter and structural network using diffusion tensor imaging (DTI) in children with type 2 and 3 SMA. Methods Forty-two type 2 and 3 pediatric SMA patients and 42 age- and gender-matched healthy controls (HC) were prospectively enrolled in this study. The tract-based spatial statistics (TBSS) was used to assess white matter integrity and the structural network properties were calculated based on DTI white matter fiber tracking and the graph theory approach. A partial correlation was performed to explore the relationship between white matter parameters and clinical characteristics. Results In total, 42 patients (mean age, 10.86 ± 4.07 years; 23 men) were included. TBSS analysis revealed widespread white matter changes in SMA patients. The SMA patients showed changes in multiple small-world and network efficiency parameters. Compared to the HC group, SMA showed increased characteristic path length (Lp), normalized clustering coefficient (γ), small-world characteristic (σ), and decreased global efficiency (Eglob) (all p < 0.05). In the node properties, right supramarginal gyrus, right orbital part of superior frontal gyrus, right supplementary motor area, and left median cingulate and paracingulate gyri changed in SMA patients. A decreased axial diffusivity (AD) value was associated with lower Hammersmith Functional Motor Scale-Expanded scores (r = 0.45, p = 0.02), which means that the symptoms of SMA patients are more severe. Conclusions This study found white matter and DTI-based brain network abnormalities in SMA patients, suggesting SMN protein deficiency may affect white matter development.